The effect of amino-functionalization on photoluminescence properties of sugarcane bagasse-derived carbon quantum dots - Nugraha, M.W. (Gadjah Mada University, 2021)
In the present study, amino-functionalized carbon quantum dots (N-CQDs) were prepared from sugarcane bagasse using a simple one-pot hydrothermal method. Both ethylenedinitrilotetraacetic (EDTA) & ethylenediamine (EDA) were used as carbon and amino sources, respectively. The emerging utilization of natural carbon precursors is critically essential considering its low cost, eco-friendly, and unexploited by-products (e.g., sugarcane bagasse), which may have sustainable economic and strategic benefits. The as-prepared N-CQDs were characterized using High-Resolution Transmission Electron Microscope (HRTEM), Fourier Transform Infrared Spectroscopy (FTIR), UV-vis absorption spectroscopy, and photoluminescence spectroscopy. The influences of amine groups were investigated. The as-prepared N-CQDs photoluminescence intensity increased and quenched significantly with EDTA and EDA amino-functionalization, respectively, was the highest quantum yield at 21.21, 2.4 times higher than non-functionalized CQDs. Furthermore, the amino-functional groups can alter the CQDs structure and particle size from 4.197±1.058 nm to 9.704±1.428 nm. Which is, the N-CQDs produced exhibit highly tunable photoluminescence and particle size, which are potentially applicable in diverse applications. © 2021, Gadjah Mada University. All rights reserved.